An Analysis of Figurative Language Used in Sing 2 Movie - Ersyaluna Salsabila Irawan; Nasrullah Nasrullah; Elsa Rosalina (Universitas Islam Negeri Palopo, 2025)
This study aims to describe the figurative language found in the Sing 2 Movie, find the meaning of each utterance, and the relationship between figurative language used in Sing 2 movie and EFL students. This type of research is descriptive qualitative research. The subject of this research is the Sing 2 movie and the figurative language are the objects. The findings of this research show that there are nine types of figurative language found in the Sing 2 Movie. They are personification, hyperbole, simile, metaphor, synecdoche, metonymy, paradox, litotes, and irony. The personification appears 6 times. The hyperbole appears 28 times. The simile appears 6 times. The metaphor appears 18 times. The synecdoche appears 2 times. The metonymy appears 1 time. The paradox appears 2 times. The litotes appears 2 times. The irony appears 3 times. The meaning of each utterance has been interpreted based on the conditions when the utterance is mentioned. This research also has benefits in fulfilling the curriculum found in schools in Indonesia. All the data were determined by the context of the situation in the movie.